2014
DOI: 10.1155/2014/965316
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritigenin Induces Tumor Cell Death through Mitogen-Activated Protein Kinase- (MPAKs-) Mediated Pathway in Hepatocellular Carcinoma Cells

Abstract: Liquiritigenin (LQ), separated from Glycyrrhiza radix, possesses anti-inflammatory, antihyperlipidemic, and antiallergic effects. Our present study aims to investigate the antihepatocellular carcinoma effects of LQ both in cell and animal models. LQ strikingly reduced cell viability, enhanced apoptotic rate, induced lactate dehydrogenase over-release, and increased intracellular reactive oxygen species (ROS) level and caspase 3 activity in both PLC/PRL/5 and HepG2 cells. The expression of cleaved PARP, the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…Bax, a proapoptotic protein, induces the threshold at which mitochondria release Cyt C to promote cell death [29]. Similarly, in another experiment, we confirmed that C. militaris induces mitochondrial apoptosis in MCF-7 and HepG2 cells related to modulation on Bcl-2 family protein expressions [30]. Oxidative stress is another factor responsible for mitochondrial function [31], during which intracellular ROS accumulation is noted.…”
Section: Discussionsupporting
confidence: 64%
“…Bax, a proapoptotic protein, induces the threshold at which mitochondria release Cyt C to promote cell death [29]. Similarly, in another experiment, we confirmed that C. militaris induces mitochondrial apoptosis in MCF-7 and HepG2 cells related to modulation on Bcl-2 family protein expressions [30]. Oxidative stress is another factor responsible for mitochondrial function [31], during which intracellular ROS accumulation is noted.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, ROS, especially superoxide anion (O 2 − ), the precursor of H 2 O 2 and OH − , not only activate cell death signaling processes but also induce other cytotoxic effects via protein, DNA, and lipid oxidation . Interesting, several studies have shown that LQ can either stimulate or inhibit apoptotic signaling . Importantly, our previous investigation found that preincubation of blastocysts with LQ clearly prevented citrinin‐induced apoptosis and impairments of preimplantation and postimplantation embryonic development, both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer activity of liquiritigenin has been observed (22). Screening for antiproliferative activity using the alamar Blue (resazurin) fluorescent cell viability measurement is relatively simple and accurate.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested some pharmacological activity for liquiritigenin including anticancer, anti-inflammatory, antidiabetic, and antioxidant activities (19202122). However, the role of each enantiomer in the pharmacological activity has not been fully evaluated.…”
Section: Introductionmentioning
confidence: 99%